2010
DOI: 10.1371/journal.pbio.1000365
|View full text |Cite
|
Sign up to set email alerts
|

Sex and the Single Cell. II. There Is a Time and Place for Sex

Abstract: In both male and female Drosophila, only a subset of cells have the potential to sexually differentiate, making both males and females mosaics of sexually differentiated and sexually undifferentiated cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
238
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(247 citation statements)
references
References 71 publications
(107 reference statements)
9
238
0
Order By: Relevance
“…3a-d). Among the dsx-expressing neuron clusters 13,14 stimulated via ChRWR, only the activation of pC1 and pC2l clusters was significantly correlated with the occurrence of both following and wing extension/vibration behaviours in courtship-like following pursuit of a multi-spot pattern (Fig. 3e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a-d). Among the dsx-expressing neuron clusters 13,14 stimulated via ChRWR, only the activation of pC1 and pC2l clusters was significantly correlated with the occurrence of both following and wing extension/vibration behaviours in courtship-like following pursuit of a multi-spot pattern (Fig. 3e).…”
Section: Resultsmentioning
confidence: 99%
“…The pC1 cluster includes a male-specific frupositive subset of cells (B20 cells), called the P1 cluster that has been shown to function as the decision-making centre for male courtship 8,17,18 . pC2l represents a non-fru-expressing sexually dimorphic cluster composed of B35 cells 13,14,19 . By examining male flies with different patterns of ChRWR expression in pC1 and pC2l clusters, the functional differences in the contribution of these two neuron groups to courtship-like behaviour were revealed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated functional contributions of Wg regulation and apoptosis to male segment reduction through misexpression of either Wg or the antiapoptotic bacculovirus gene p35. Two Dsx-gal4 drivers have been reported with dynamic expression throughout larval, pupal, and adult tissues (38,39). Importantly for our assays, these drivers are expressed throughout the developing imaginal abdomen epithelium.…”
Section: Roles Of Wingless and Apoptosis In Male Segmentmentioning
confidence: 93%
“…In addition, the recent finding that developing Drosophila are mosaic for dsx expression-and thus are mosaic for the potential for sexual differentiation-has led to increased appreciation for the potential of evolution through tissuespecific changes in dsx activity (15). Indeed, it was recently found that the diversification of sex combs in Drosophila species is correlated with changes in dsx expression patterns (14).…”
mentioning
confidence: 99%